Social emotional health, life satisfaction and school climate of junior school students in the context of Covid-19 pandemic crisis - Petrulyte, Ala (Psihološka obzorja (Ljubljana), 2022)
Research on students’ social-emotional health is important for quality learning and well-being at school, especially during the challenges of the Covid-19 pandemic times. Purpose: to investigate younger school-age students’ social-emotional health, satisfaction with life, and perceived school climate in the Covid-19 pandemic crisis and the predominance of distance learning by longitudinal research strategy. Method: Social and Emotional Health Survey-Primary (SEHS-P; Furlong et al., 2013) and Multidimensional Students Life Satisfaction Scale (MSLSS; Huebner, 2001). The sample was 84 junior school-age students (10 –12 years old) from Lithuanian schools. The results and conclusions: The first months of the Covid-19 pandemic crisis led to the deterioration of socialemotional health and satisfaction of younger school-age students. However, after 8 months of the Covid-19 pandemic crisis (re-test), some improvements in students’ emotional health, satisfaction with life, and classroom microclimate were observed. No gender-based differences were identified among students. The results revealed positive and significant correlations between the younger school-age students’ social-emotional health, satisfaction with life, and perceived school climate; the conducted regression analysis showed that family plays a significant role in junior school students’ social-emotional health. The teachers’ support for distance learning students could have improved their classroom microclimate and the knowledge of students’ health status could have helped them to adapt to distance learning more effectively during the Covid-19 pandemic crisis.
Keywords: COVID-19; duševno zdravje; izobraževanje; Litva; pouk na daljavo; šolska klima; učenci; vzgoja